(untitled) (Journal of Hama University, 2024)
The research aimed to determine the role of brainstorming in its stages (the problem identification and formulation stage, the problem crystallization stage, the idea induction stage, and the proposed ideas stage) as one of the methods for choosing performance measurement indicators in improving health performance (quantity of work, quality of work completed) for public hospitals on the Syrian coast, The research relied on the descriptive approach to describe and analyze the research variables based on the primary data collected. The researcher conducted a field study on public hospitals on the Syrian coast to collect the necessary primary data. The variables were also measured on all the primary data that was collected through a questionnaire designed by During the researcher’s review of previous studies and literature, and in order to test the hypotheses, the researcher transcribed the raw data into a database that was analyzed using SPSS version 20. The research reached a number of results, including: There is a significant relationship between brainstorming and its stages (the stage of identifying and formulating the problem, the stage of crystallizing the problem, the stage of inducing ideas, and the stage of proposed ideas) and one of the methods for choosing performance measurement indicators and improving health performance (quantity of work, quality of work completed) for public hospitals on the Syrian coast, The worker is not keen to complete the work without errors.